Unge og selvskade: Resultater fra en dansk national repræsentativ undersøgelse i 2008 - Larsen, Helmer Bøving (Psyke & Logos, 2016)
In a nationwide school survey in 2008 conducted by use of multi-media computer assisted self-interviewing, prevalence rates of suicidal attempts and non-suicidal self-injury were assessed among 1,991 boys and 1,942 girls in 9th grade and correlated to comprehensive information on the adolescents’ family, social contacts, exposure to physical violence, sexual abuse and to other adverse experiences and their self-assessed mental health. One in five girls and one in ten boys reported fantasies about self-harm, suicidal intention or non-suicidal self-injury during the past week. Among boys, self-harm was correlated to adverse experiences: sexual abuse, intra-family violence and lack of confidence to parents. Depression was correlated to girls’ self-harm and suicidal intention. Prevention of self-harm should build on the development of programs that address the psychosocial, family and related factors that apparently contribute to the risk of selfharm.